Mucosal cancer-associated microbes and anastomotic leakage after resection of colorectal carcinoma. (March 2020) - Mima, Kosuke; Sakamoto, Yuki; Kosumi, Keisuke; Ogata, Yoko; Miyake, Keisuke; Hiyoshi, Yukiharu; Ishimoto, Takatsugu; Iwatsuki, Masaaki; Baba, Yoshifumi; Iwagami, Shiro; Miyamoto, Yuji; Yoshida, Naoya; et al.
Abstract: Background: Clinical and experimental evidence suggests that colorectal mucosal microbiota changes during colorectal carcinogenesis and may impair colorectal anastomotic wound healing. Thus, we hypothesized that amounts of colorectal cancer-associated microbes in colorectal tissue might be associated with anastomotic leakage after resection for colorectal carcinoma. Methods: We analyzed 256 fresh frozen tissues of colorectal cancer from patients who underwent elective colorectal resection and anastomosis. Amounts of colorectal cancer-associated microbes, including Fusobacterium nucleatum, Escherichia coli possessing the polyketide synthase (pks) gene cluster, Enterococcus faecalis, and Bifidobacterium genus, in colorectal cancer tissues were measured by quantitative polymerase chain reaction assay; we equally dichotomized positive cases (high versus low). Multivariable logistic regression analysis was conducted to assess associations of these microbes with anastomotic leakage, adjusting for patient and tumor characteristics, and surgery-related factors. Results: Fusobacterium nucleatum, pks-positive Escherichia coli, Enterococcus faecalis, and Bifidobacterium genus were detected in colorectal carcinoma tissue in 140 (54%), 94 (36%), 193 (75%), and 89 (35%) of 256 cases, respectively. Compared with Bifidobacterium genus-negative cases, Bifidobacterium genus-high cases were associated with an increased risk of anastomotic leakage (multivariable odds ratio, 3.96; 95% confidence interval, 1.50 to 10.51; P trend  = 0.004). The association of Fusobacterium nucleatum, pks-positive Escherichia coli, or Enterococcus faecalis with anastomotic leakage was not statistically significant. Conclusions: The amount of Bifidobacterium genus in colorectal tissue is associated with an increased risk of anastomotic leakage after resection for colorectal cancer. These findings need to be validated to target gastrointestinal microflora for the prevention of anastomotic leakage after colorectal resection. Highlights: Experimental evidence from animal models indicates that colorectal mucosal microbes can impair colorectal anastomotic wound healing after colorectal resection. Higher amounts of colorectal cancer-associated microbes, such as Bifidobacterium genus, in colorectal mucosal tissue were associated with an increased risk of anastomotic leakage after resection for colorectal cancer. Upon validation, colorectal mucosal microbes may serve as potential targets for the prevention of anastomotic leakage after colorectal resection.